Profit Efficiency Among Jhum Practicing Tribal People of Mizoram State - Lalrinsangpuii; R. Malhotra; Laishram Priscilla; and Bulbul G. Nagraleome (Ind. Jn. of Agri. Econ., 2016)
The present study was undertaken in Mizoram state to study the profit efficiency in jhum farming on sample households using a Translog stochastic profit frontier and inefficiency model. The primary data were collected from 120 sample dairy farmers in the three districts of Mizoram, viz., Aizawl, Kolasib and Champhai during 2014-15 using structured interview schedule. The results showed that profit efficiencies of the sample farmers varied widely between 31 and 78 per cent with a mean of 55 per cent suggesting that an estimated 45 per cent of the profit was lost due to a combination of both technical and allocative inefficiencies. The study further observed that farming experience, size of the farm and non-farm income influenced profit efficiency positively while profit efficiency decreased with age. The results found a considerable capacity to improve profitability of jhum farmers in the state. The study recommends that the inputs should be made available to farmers at competitive prices and the quantity of labour use should be decreased because the current level is incompetitive. Training should also be provided to farmers to enable them to adopt the best jhum farming practices.